Membrane behavior and diffusion in unsaturated sodium bentonite - Sample-Lord, Kristin M., author; Shackelford, Charles D., advisor; Bareither, Christopher A., committee member; Butters, Gregory L., committee member; Lu, Ning, committee member; Sale, Thomas C., committee member (Colorado State University. Libraries, 2015)
Sodium-bentonite (Na-bentonite) is a highly active clay commonly used as a barrier or a component of a barrier for chemical containment applications (e.g., landfills, waste impoundments, vertical cutoff walls) due to the ability of Na-bentonite to limit solute (contaminant) transport resulting from high swell and low hydraulic conductivity. However, Na-bentonite also may exhibit semipermeable membrane behavior or solute restriction, which can result in enhanced performance of the barrier by reducing liquid and contaminant flux. Experimental studies to date have focused on the correlation between membrane behavior and diffusion of solutes almost exclusively under fully saturated conditions (i.e., degree of water saturation, S, of 1.0). However, clay barriers can exist at various degrees of water saturation (S < 1.0), and, based on our current, conceptual understanding of the mechanisms causing membrane behavior in saturated clays, the influence of membrane behavior on solute transport is likely to be even more significant in clays under unsaturated conditions. Based on these considerations, an innovative testing apparatus was developed to allow for the simultaneous measurement of membrane behavior and diffusion in unsaturated Na-bentonite. The test specimens were prepared using a dialysis method that allowed for control of the cation species on the exchange complex of the bentonite, removal of excess soluble salts, and estimation of diffusion properties. Membrane efficiencies (ω) and effective diffusion coefficients (D*) of bentonite specimens with S ranging from 0.79 to 1.0 were measured by performing multistage tests using solutions of potassium chloride (KCl). The source concentrations (Cot) of the KCl solutions were 20 mM, 30 mM, and 50 mM, which resulted in average concentrations in the specimen at steady-state diffusion (Cave) of approximately 10 mM, 15 mM, and 25 mM. For all values of S, a decrease in S correlated with an increase in ω and a decrease in D*. For example, for Cot of 50 mM, ω increased from 0.31 to 0.41 and D* for chloride decreased from 4.1 x 10-10 m2/s to 3.1 x 10-10 m2/s as S decreased from 1.0 to 0.84. The results of this study advance our fundamental understanding of solute transport mechanisms in Na-bentonite and contribute to the base of knowledge that must be established prior to incorporating membrane behavior effects in the design of barriers for chemical containment facilities.
Keywords: clay; membrane behavior; bentonite; unsaturated; diffusion